Effects of Intra-articular Magnesium Sulfate Injection in Post-operative Pain in Knee Arthroscopy: A Prospective Comparative Study - Toloueghamari, Babak (Asian Journal of Pharmaceutics (AJP), 2017)
Background and Objective: Intra-articular magnesium sulfate, an N-methyl-d-aspartate receptor blocker, would be of particular interest in either producing post-operative analgesia or enhancing the analgesic effect of intra-articular bupivacaine. This study was aimed to investigate the efficacy of intra-articular magnesium sulfate injection as post-operative analgesic agent knee arthroscopy. A decrease in visual analog scale (VAS) score followed by a decrease in analgesic requirement and subsequently less analgesic requirement. Materials and Methods: This is a randomized, prospective, double-blinded clinical trial conducted on patients undergoing arthroscopic partial meniscectomy referred to Ahvaz Razi Hospital, Iran. 94 patients were randomly divided into two parallel groups. The saline placebo group received 20 ml of isotonic saline, and the magnesium sulfate group received 20 ml of isotonic saline containing 1 g magnesium sulfate. The post-operative analgesia was assessed using VAS recorded at 5, 60, 120, and 240 min post-surgery. Patients were evaluated at rest and under movement. Results: The magnesium sulfate group showed a significant reduction in VAS score, a significantly increased time to first post-operative analgesic request, as well as significantly reduced total analgesic requirement than the control group. Conclusion: Magnesium sulfate produces a reduction in post-operative pain when given intra-articularly in comparison to saline placebo.